Enhancing the Effectiveness of a Professional Pest Management Program - Frederick M. Fishel (EDIS)
The purpose of this guide is to provide information that will optimize pest control in the home environment when working with a professional pest control operator. This document is PI-39, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2005.